Relationship between age and elite marathon race time in world single age records from 5 to 93 years - Knechtle, B.; Assadi, H.; Lepers, R.; Rosemann, T.; Rüst, C. A. (BMC Sports Science, Medicine and Rehabilitation, 2014)
Background: The aims of the study were (i) to investigate the relationship between elite marathon race times and age in 1-year intervals by using the world single age records in marathon running from 5 to 93 years and (ii) to evaluate the sex difference in elite marathon running performance with advancing age.